Pronomina Bahasa Kadai - Noormala Noormala (Kantor Bahasa Provinsi Maluku Utara, 2016)
Kadai is one of vernacular language found in North Maluku that spoken by Kadai etnic. This paper aims at to describe the pronoun of Kadai language. Collective data is done by using observation method, interview method, and evaluation method. Those collective data is then analyized by structural approachment and distributional method by using basic and contininou technique. The result shows that Kadai has the pronoun of noun, namely aku ‘I’, io ‘she/he/it’, kami ‘we’, kito ‘we’, kou ‘you’, ke ‘you’, dan matu ‘they’, demonstrative pronoun, namely yai ‘this/that’ and yo ‘those/these’, and introgative pronoun, namely woi ‘who’ and mansa ‘what’.